Fourteen-year trends in overweight, general obesity, and abdominal obesity in Amazonian indigenous peoples - Eliniete de Jesus Fidelis Baniwa; Eliene Rodrigues Putira Sacuena; Rosilene Reis Della Noce; Vanessa Barroso Quaresma; Teodora Honorato Alencar; Renan Barbosa Lemes; Antônia Cherlly Araújo; Izaura Maria Vieira Cayres-Vallinoto; João Farias Guerreiro (BMC, 2024)
Abstract Background Available data show that the epidemiological profile of most indigenous Brazilian populations is characterized by the coexistence of long-standing health problems (high prevalence of infectious and parasitic diseases, malnutrition, and deficiency diseases, such as anemia in children and women of reproductive age), associated with new health problems, especially those related to obesity (hypertension, type 2 diabetes mellitus and dyslipidemia). Based on this scenario, this study analyzed the nutritional profile of the adult population of seven indigenous peoples from the Brazilian Amazon in the years 2007 and 2021. Methods A total of 598 adults individuals were analyzed in 2007 (319 women and 279 men) and 924 in 2021 (483 women and 441 men), from seven indigenous peoples located in the state of Pará, who were assisted during health actions carried out in 2007 and in 2021. Body mass index classification used the World Health Organization criteria for adults: low weight, < 18.5 kg/m2; normal weight, ≥ 18.5 and < 25 kg/m2); overweight, ≥ 25 and < 30 kg/m2, and obesity, ≥ 30 kg/m2. A waist circumference (WC) < 90 cm in men and < 80 cm in women was considered normal. Results The data revealed heterogeneous anthropometric profiles, with a low prevalence of nutritional changes in the Araweté, Arara and Parakanã peoples, and high proportions of excess weight and abdominal obesity in the Kararaô, Xikrin do Bacajá, Asurini do Xingu and Gavião peoples, similar to or even higher than the national averages. Conclusion Different stages of nutritional transition were identified in the indigenous peoples analyzed, despite apparently having been subjected to the same environmental pressures that shaped their nutritional profile in recent decades, which may indicate different genetic susceptibilities to nutritional changes. The evidence shown in this study strongly suggests the need to investigate in greater depth the genetic and environmental factors associated with the nutritional profile of Brazilian indigenous peoples, with assessment of diet, physical activity and sociodemographic and socioeconomic variables that enable the development of appropriate prevention and monitoring measures.